Randomized pilot trial of praise text messages to improve medication adherence among adolescents and young adults with liver transplants. (19th July 2022) - Sayegh, Caitlin; Im, Deborah; Moss, Ilana K.; Urquiza, Ruby; Patel, Shreena; Thomas, Dan W.
Abstract: Background: AYA who have undergone liver transplantations often struggle to adhere to their post‐transplant immunosuppressant medications, which can lead to serious health complications. The objective of this pilot study is to examine the acceptability and feasibility of a brief mobile health (mHealth) intervention and its impact on medication adherence among AYA liver transplant recipients. Methods: Thirty‐five AYAs (13–21 years old) were randomized to either (1) receive praise text messages whenever laboratory results indicated immunosuppressant medications within the expected range or (2) usual care. Motivation for adherence and adherence were assessed via self‐report, and a MLVI was calculated based on values abstracted from the electronic health record. Results: Multilevel, multivariate models showed significant associations between group assignment and some self‐reported motivation and adherence outcomes but not MLVI. Specifically, AYA receiving the praise text messages were significantly more likely to report taking their prescribed doses (OR = 2.49, p  = .03), taking their medicine according to the directions (OR = 2.39, p  = .04), and being highly confident in taking their medication (OR = 2.46, p  = .04), compared with the usual services group. Qualitative responses indicated praise texts were mostly helpful but could be improved. Conclusions: The results suggest texting patients about positive health indicators was acceptable and, with refinement, might promote AYA illness self‐management.